On the asymptotic behaviour of some functionals of the Brownian motion process - Skorokhod , A. V.; Slobodenyuk, N. Р.; Скороход, А. В.; Слободенюк, Н. П. (Institute of Mathematics, NAS of Ukraine, 1966)
-